2015
DOI: 10.1007/s40265-014-0340-3
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab: A Review of Its Use in Patients with Chronic Lymphocytic Leukaemia

Abstract: Obinutuzumab (Gazyva(®); Gazyvaro(®)) is an intravenously administered, glycoengineered, humanized, type II, anti-CD20 monoclonal antibody of the IgG1 subclass. It is available in the EU and the USA as combination therapy with oral chlorambucil in adults with previously untreated chronic lymphocytic leukaemia (CLL). In a multinational phase III study in this patient population, obinutuzumab plus chlorambucil significantly prolonged progression-free survival compared with oral chlorambucil alone and intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…They contain proteins and RNAssuch as microRNAs (miRNAs)which are taken up by nearby and distant cells, thereby enabling genetic material and signalling proteins to be transferred among cells. 1,2 The role of exosomes in patients with haematological malignancies has not been studied as extensively as in solid cancers. The limited information available indicates that exosomes play roles in cell development, functional integrity, and progression to haematological malignancy.…”
Section: The Exosomal Surface Phenotype and Inflamma-mir Cargo Correlmentioning
confidence: 99%
See 1 more Smart Citation
“…They contain proteins and RNAssuch as microRNAs (miRNAs)which are taken up by nearby and distant cells, thereby enabling genetic material and signalling proteins to be transferred among cells. 1,2 The role of exosomes in patients with haematological malignancies has not been studied as extensively as in solid cancers. The limited information available indicates that exosomes play roles in cell development, functional integrity, and progression to haematological malignancy.…”
Section: The Exosomal Surface Phenotype and Inflamma-mir Cargo Correlmentioning
confidence: 99%
“…Obinutuzumab is a type II, glycoengineered, humanized anti-CD20 monoclonal antibody, with enhanced direct cell death and antibody-dependent cell-mediated cytotoxicity. 1 Obinutuzumab is FDA-approved for chronic lymphocytic leukaemia (CLL) in combination with chlorambucil, ibrutinib or venetoclax as a first-line treatment. [2][3][4] Similar to rituximab, obinutuzumab induces B-cell depletion and reduced antibody production, granting it the potential to effectively treat antibody-mediated autoimmune phenomena.…”
mentioning
confidence: 99%
“…GA101 was shown to exert cytotoxicity in RTX-resistant cell lines [156,157]. Most recently, obinutizumab has been approved for the first-line treatment of less-fit CLL patients [158]. …”
Section: Other Anti-cd20 Moabsmentioning
confidence: 99%
“…Obinutuzumab (GA101) is a Type II humanized mouse IgG1κ anti-CD20 antibody with a glycoengineered Fc fragment [15] to enhance Fc receptor binding affinity (in particular for FcγRIIIa). GA101 is currently under phase III clinical trials for the treatment of patients with NHL [16,17] and has been approved for patients with previously untreated CLL [18][19][20][21]. In vivo studies have indicated superior anti-lymphoma activity for this third-generation anti-CD20 antibody over rituximab [15,22,23].…”
Section: Introductionmentioning
confidence: 99%